Perubahan Perilaku Masyarakat Ponorogo dalam Menyelenggarakan Pernikahan di Era Pandemi Covid-19 - Ayu Nur Indah Sari (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2021)
Abstract: Indonesia is one of the countries affected by the spread of the corona virus. This has led to various changes in society, one of the things that is affected is the implementation of marriage. This study uses a qualitative method by collecting data through documentation from several online news, Ponorogo district government regulations and direct observations in the community. The findings in this study indicate changes that occur in the implementation of marriages in the Ponorogo community, this is done to reduce the spread of the covid-19 virus and as a manifestation of benefit which is an essential value in maqashid sharia.